Critical review: the effectiveness of student teams-achievement divisions vs numbered heads together cooperative learning in improving students' mathematical critical thinking abilities - Suharli, Suharli; Kusmawan, Udan; Sudirman, Sudirman (Gema Wiralodra, 2024)
This research aims to analyze the differences in critical mathematical thinking abilities who receive cooperative learning in the Student Teams-Achievement Divisions (STAD) type and those who undertake the cooperative learning process in the Numbered Head Together (NHT) type. This research design uses a quasi-experimental design. Apart from that, the population in this study were all students of the Taliwang State 1 Middle School West Sumbawa, while the sample was taken in two classes randomly from 18 existing classes (class VIII 3 and class VIII 4). Experimental class 1 consists of 32 people, while experimental class 2 consists of 32 people, so the total is 64 people. Data obtained from thinking ability tests were analyzed univariately, bivariate, and multivariate. The results of the univariate analysis show that the majority of respondents in Experiment 1 were male, 16 females, 16 people each (50%), the majority were of medium ability, 21 people (65.6%), then the High category was 7 people (22%) and the low category as many as 4 people (12.5%), while the majority of respondents in Experiment 2 were 17 people (53.1%) women while 15 people (47%) were men with 17 people (53.1%) in the medium category. High 9 people (28.1% and Low category 6 people (18.7%). Furthermore, the results of bivariate analysis showed that there were differences in students' mathematical critical thinking abilities between experimental class 1 and experimental class 2, while the significant value for the group category was 0.007, this means that there are differences in students' mathematical critical thinking abilities based on the categories of high, medium and low ability students. The results of the multivariate analysis show that the mathematical critical thinking abilities of students who received STAD-. type cooperative learning has a higher increase than students who receive NHT-type cooperative learning.